Improving Problem-Solving Skills through the Implementation of PBL-Based IPAS Instructional Videos - Ni Putu Kaori Candra Devi; Maria Goreti Rini Kristiantari; Komang Sujendra Diputra (Universitas Pendidikan Ganesha, 2025)
The low problem-solving ability of students in understanding economic activity concepts, along with the lack of relevance between the material and real-life contexts, poses a challenge in teaching Science and Social Studies (IPAS) at the elementary school level. To address this issue, this study developed a Problem-Based Learning (PBL)-based instructional video that connects the material with local wisdom. The study employed a Research and Development (R&D) method using the ADDIE model, involving 38 fourth-grade elementary students, subject matter experts, design experts, and instructional media experts. Data were collected through validation questionnaires, student comprehension tests, and observations. The data analysis techniques used included quantitative descriptive analysis to assess media validity and a t-test to measure its effectiveness. The results showed that the PBL-based instructional video had a very high level of validity, with an average rating above 90%. Furthermore, the t-test results indicated a significant difference between students’ pre-test and post-test scores (tvalue = 9.620 > ttable = 1.687), demonstrating its effectiveness in improving students’ problem-solving skills. In conclusion, the integration of PBL with instructional video has proven to be an innovative solution in IPAS learning, helping students understand economic concepts through real-life contexts and local wisdom, as well as enhancing their critical thinking skills.